Dietary Lactobacillus plantarum Relieves Nile Tilapia (Oreochromis niloticus) Juvenile From Oxidative Stress, Immunosuppression, and Inflammation Induced by Deltamethrin and Aeromonas hydrophila - Gewaily, Mahmoud S.; Shukry, Mustafa; Abdel-Kader, Marwa F.; Alkafafy, Mohamed; Farrag, Foad A.; Moustafa, Eman M.; Doan, Hien Van; Abd-Elghany, Mohamed F.; Abdelhamid, Ahmed F.; Eltanahy, Azhar; Dawood, Mahmoud A. O. (Frontiers in Marine Science, 2021)
Aeromonas hydrophila infection is one of the major diseases which causes inflammation and immunodepression in aquatic animals. Likewise, waterborne toxins are known for their negative impact on the immunity and antioxidative responses of aquatic organisms. In this study, immunobiotics (LP20) were incorporated in Nile tilapia diets to investigate its role in the antioxidation, immunity, and anti-inflammation induced by deltamethrin toxicity (DLM) and A. hydrophila. Fish were allocated in four groups where the control group did not receive LP20 nor exposed to DLM, and the second group fed the control and exposed to DLM (DLM). The third group provided LP20 without DLM toxicity (LP20), and the fourth group fed LP20 AND exposed to DLM (DLM+LP20). After 30 days, fish were intraperitoneally injected with A. hydrophila. Ten days post-infection, the survival rate displayed the lowest rate in fish suffered from DLM, while the highest rate was noticed in the LP20 group. Further, the group of fish fed LP20 had the most elevated serum total protein (sTP), albumin (ALB), globulin (GLB), phagocytic index (PI), phagocytic (PA), lysozyme activities (LZM), and the lowest urea, uric acid bilirubin, creatinine, glucose, ALT, AST, and ALP. However, fish under DLM toxicity had the lowest sTP, ALB, GLB, and the highest urea, uric acid, bilirubin, creatinine, glucose, ALT, AST, and ALP after 24 hours, 48 hours, and 1-week post A. hydrophila challenge. Markedly, the transcription of antioxidative (SOD, CAT, and GPx) genes were expressed in tilapia of the DLM+LP20 group. Also, tilapia under DLM toxicity showed upregulated IFN-γ, IL-12, TNF-α, and HSP70 genes. Besides, severe inflammatory features were observed in the liver, spleen, gills, and intestine of tilapia under DLM toxicity and A. hydrophila infection, while LP20 resulted in anti-inflammation results. In summary, immunobiotics (LP20) relieved the oxidation, immunosuppression, and inflammation in Nile tilapia induced by DLM toxicity and A. hydrophila infection.